A QUALITATIVE AND QUANTITATIVE ANALYSIS OF EXTRACTIVES FROM THE SPECIES Trifolium pratense L. IN THREE DIFFERENT SOLVENTS - Chavenetidou, Marina A; Pankou, Chrysanthi I; Tziouvalekas, Miltiadis S (Poljoprivreda i šumarstvo, 2021)
(2014), investigated the chemical constituents of the essential oils coming from Trifolium pratense in three different growth stages to test them for their antioxidant and antimicrobial activities, with the use of gas chromatography-mass spectrometry. [...]they were weighed to determine the dry weight of the extracted (wood) material, after the removal of the extractives (Chavenetidou, 2009). [...]the mass spectrometer with quadrupole Agilent 5975C was also implemented and 1bromo-2-nitrobenzene was used as internal standard for the estimation of the quantity (Tziouvalekas, 2011). According to the analysis of variance (Table 3), statistically significant differences were revealed between the amount of extracts released in the three different solvents that were used. [...]the part of the plant that was used for the analysis also played a crucial role as the differences between them were also statistically significant, although